2016
DOI: 10.1186/s12866-016-0824-2
|View full text |Cite
|
Sign up to set email alerts
|

The SAV1322 gene from Staphylococcus aureus: genomic and proteomic approaches to identification and characterization of gene function

Abstract: BackgroundBacterial two-component regulatory systems (TCRS) are associated with the expression of virulence factors and antibiotic susceptibility. In Staphylococcus aureus, 16 TCRS types have been identified. The histidine kinase/response regulator SAV1321/SAV1322 in the S. aureus shares considerable homology with the TCRS DesKR in Bacillus subtilis. However, a function for the SAV1322 locus has not yet been assigned.ResultsDeletion of the SAV1322 locus in S. aureus results in reduced growth when cultured unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Previous GWAS of vancomycin MIC have shown the role of known determinants of vancomycin resistance including walKR (Baines, Holt et al 2015), rpoB (Alam, Petit et al 2014). Here, in a large GWAS of vancomycin MIC, we confirm the role of some of these established determinants of vancomycin resistance (walK, mprF), and provide evidence for new loci, the most promising being desR, a response regulator (Kim, Kim et al 2016) that was recently singled out in a screening for targets of an antivirulence molecule that is able to reverse beta-lactam resistance in MRSA strains (El-Halfawy, Czarny et al 2020). Our results confirm the potential for bacterial GWAS to assist the discovery of non-canonical antibiotic resistance loci (Farhat, Freschi et al 2019).…”
Section: Discussionsupporting
confidence: 77%
“…Previous GWAS of vancomycin MIC have shown the role of known determinants of vancomycin resistance including walKR (Baines, Holt et al 2015), rpoB (Alam, Petit et al 2014). Here, in a large GWAS of vancomycin MIC, we confirm the role of some of these established determinants of vancomycin resistance (walK, mprF), and provide evidence for new loci, the most promising being desR, a response regulator (Kim, Kim et al 2016) that was recently singled out in a screening for targets of an antivirulence molecule that is able to reverse beta-lactam resistance in MRSA strains (El-Halfawy, Czarny et al 2020). Our results confirm the potential for bacterial GWAS to assist the discovery of non-canonical antibiotic resistance loci (Farhat, Freschi et al 2019).…”
Section: Discussionsupporting
confidence: 77%
“…In contrast, the exoproteome is a true indicator of virulence factor levels, and potentially Sa pathogenesis (64). We and others have successfully exploited this strategy to study Sa virulence properties (42,65,66). However, these studies have largely compared exoproteomes…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted on S. aureus have demonstrated that mutants of the DesKR TCS exhibit higher tolerance to oxidative stress. However, these mutants also display increased autolysis, thinner cell walls, reduced antibiotic resistance, and lower pathogenicity in vivo ( 64 ). The role of DesKR in temperature adaptation and antibiotic resistance has been well established, particularly in terms of how temperature sensing affects its sensor-regulator interaction dynamics and physiological function ( 65 , 66 ).…”
Section: Discussionmentioning
confidence: 99%